Twentieth-century Spain a history - Casanova, Julián; Gil Andrés, Carlos; Douch, Martin (Cambridge Cambridge University Press, 2014)
"This is a much-needed new overview of Spanish social and political history which sets developments in twentieth-century Spain within a broader European context. Julián Casanova, one of Spain's leading historians, and Carlos Gil Andrés chart the country's experience of democracy, dictatorship and civil war and its dramatic transformation from an agricultural and rural society to an industrial and urban society fully integrated into Europe. They address key questions and issues that continue to be discussed and debated in contemporary historiography, such as why the Republic was defeated, why Franco's dictatorship lasted so long and what mark it has left on contemporary Spain. This is an essential book for students as well as for anyone interested in Spain's turbulent twentieth century"--Provided by publisher.
"Alcala Zamora, Niceto (1877-1949). A liberal politician during the Restoration. In 1930, following the fall of Primo de Rivera's dictatorship, he declared himself to be anti-monarchist and took part in the Pacto de San Sebastian. After the municipal elections of 14 April 1931 he headed the first provisional government of the Republic. He was President of the Second Republic between 1931 and April 1936. At the end of the Civil War, he was forced to go into exile, firstly in France and then in Argentina, where he died"--Provided by publisher.
Part I. The monarchy of Alfonso XIII -- Part II. The second republic -- Part III. The Civil War -- Part IV. Franco's dictatorship -- Part V. Transition and democracy.
Includes bibliographical references and indexes.
Keywords: Spain -- History -- 20th century